PERSPEKTIF HEDONIC SHOPPING MOTIVATION DALAM MENDORONG IMPULSE BUYING BEHAVIOUR PADA KONSUMEN PRODUK KOSMETIK WATSON INDONESIA - Rimadias, Santi; Lubis, Maryam Asiah (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This research aims to analyze the perspective of Hedonic Shopping Motivation consisting of Novelty, Fun, Appraise from Other, Escapism, Social Interaction and Desire for Visual Aesthetics on Impulse Buying Behaviour on cosmetics product consumers of Watson Indonesia. Design/methodology/approach- The survey involved 195 respondents who has purchased cosmetics product in Watson Indonesia using structured questionnaires. Construction is measured by using the specified scale. Multiple regression was used to analyse the data. Findings- The results showed that all variables in theperspective of Hedonic Shopping Motivation such as Novelty, Appraise from Other, Escapism, Social Interaction and Desire for Visual Aesthetics had a positive influence on Impulse Buying Behaviour, except Fun. Implication/Limitations- The implications of this research are the reference for marketers in formulate strategies to drive impulse buying behaviour to consumer cosmetic products related to the perspective of hedonic shopping motivation. Keywords: Novelty, Fun, Appraise from Other, Escapism, Social Interactions, Desire for Visual Aesthetics, Impulse Buying Behaviour.